2014 International Conference on Probabilistic Methods Applied to Power Systems (PMAPS) 2014
DOI: 10.1109/pmaps.2014.6960619
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wide-area availability of wind generators during storm events

Abstract: During high wind speed shutdown (HWSS) events, the power outputs of wind power plants may be subject to high ramp rates, causing issues for the System Operator (SO) in predicting total wind output, allocating adequate reserve levels and minimising balancing costs. As the timing of these events is difficult to predict, it is proposed that individual turbines may be used as probabilistic early warning indicators of HWSS events across sites, and by extension to a wide geographical area. The shut-down history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Various different approaches have been tried, but the scarcity of data remains a challenge when it comes to modelling wind farm output in adverse conditions. Examples of work completed in this area can be seen in [11, 30]. In the former, data analysis studied the availability of a wind farm as storm‐fronts passed across it to determine the impact of HWSS, whereas in the latter, HWSS was evaluated by generating a power curve from wind speed data compared to aggregated wind power outputs in GB; due to the scarcity of wind speed/output data at high speeds, a Gaussian filter was fitted by inspection to the tail of the data to represent HWSS.…”
Section: Effects Of Wind Speed On Wind Power Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…Various different approaches have been tried, but the scarcity of data remains a challenge when it comes to modelling wind farm output in adverse conditions. Examples of work completed in this area can be seen in [11, 30]. In the former, data analysis studied the availability of a wind farm as storm‐fronts passed across it to determine the impact of HWSS, whereas in the latter, HWSS was evaluated by generating a power curve from wind speed data compared to aggregated wind power outputs in GB; due to the scarcity of wind speed/output data at high speeds, a Gaussian filter was fitted by inspection to the tail of the data to represent HWSS.…”
Section: Effects Of Wind Speed On Wind Power Outputmentioning
confidence: 99%
“…These are generally considerate only of wind speeds experienced at nodes rather than localised weather conditions, which can vary significantly across network branches. Wind power output, too, can also be significantly affected by extreme wind as storms pass across wind farms and regions [11]. Therefore, wind‐related risk on overhead lines (OHLs) and wind power output are intrinsically linked concepts but in order to fully understand the interaction between these elements there needs to be an appropriately disaggregated spatiotemporal analysis.…”
Section: Introductionmentioning
confidence: 99%
“…When storms cause damage of wind turbines, shutdown may last for long time. Considering two WFs, "A" with 60 wind turbines and "B" with 28, Macdonald et al, [18] found out percentage of incidents of 50% and 100% loss of availability of WFs "A" and "B", due to high wind speed shutdown (HWSS). They stated that, for WF "A", 15.8% of HWSS incidents for the period 10 th January 2010 -12 th August 2013, approximately resulted in loss of at least 50% turbine availability.…”
Section: Characteristics Of Ress and Evsmentioning
confidence: 99%
“…In the context of frequency stability, High Wind Speed Shutdown (HWSS) represents a high-risk scenario as large, rapid power swings are possible when multiple turbines shut down within quick succession (Coughlan et al, 2012;Detlefsen et al, 2011;MacDonald et al, 2014). HWSS is a protection feature employed on most wind turbines, which results in the sudden curtailment of generation when turbines are exposed to high wind speeds (Coughlan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Cutululis et al (2013), for example, reported that 1500 MW is at risk within a time frame of 30 minutes for the worst-case scenario for the Danish power system. MacDonald et al (2014) analysed the operational data from two wind farms situated approximately 180 km apart from one another. Complete shutdown of the windfarms occurred, on average, approximately 5% to 10% of the time when HWSS events occurred.…”
Section: Introductionmentioning
confidence: 99%